2005
DOI: 10.2166/wst.2005.0191
|View full text |Cite
|
Sign up to set email alerts
|

Start-up of moving bed biofilm reactors for deammonification: the role of hydraulic retention time, alkalinity and oxygen supply

Abstract: Aerobic and anaerobic ammonium oxidation can be combined in a completely mixed moving bed biofilm reactor, allowing for single-stage ammonium removal from wastewater with low COD/N ratio unsuitable for conventional nitrification/denitrification processes (‘deammonification’). Mandatory preconditions are: (a) a low hydraulic retention time to wash out suspended cells competing with mass transfer limited biofilm cells for alkalinity as limiting substrate; and (b) an oxygen flux adapted to the surface loading rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(22 citation statements)
references
References 0 publications
1
20
0
1
Order By: Relevance
“…The free-water surface wetlands had low redox potentials and dissolved oxygen concentrations (Table 1), indicating conditions that were suitable for coupling partial nitrification and anammox (Gaul et al, 2005;Tao et al, 2011;van der Star et al, 2007). Microorganisms in free-water surface wetlands may attach to sediment particles, plant stems, and litter, forming biofilms.…”
Section: Microbial Processes For Nitrogen Removalmentioning
confidence: 99%
“…The free-water surface wetlands had low redox potentials and dissolved oxygen concentrations (Table 1), indicating conditions that were suitable for coupling partial nitrification and anammox (Gaul et al, 2005;Tao et al, 2011;van der Star et al, 2007). Microorganisms in free-water surface wetlands may attach to sediment particles, plant stems, and litter, forming biofilms.…”
Section: Microbial Processes For Nitrogen Removalmentioning
confidence: 99%
“…7) was constructed to show the phylogenetic relationships between the two anammox microorganisms detected in the systems and other anammox microorganisms including ''Brocadia fulgida'' and Candidatus ''Kuenenia stuttgartiensis''. Gaul et al (2005) have suggested that Brocadia strains, e.g. ''Brocadia anammoxidans'' strains are highly inhibited by elevated NO 2 -concentrations, and therefore they are not enriched in reactor systems of high -concentration, which temporarily occurred in our system.…”
Section: Pcr and Dgge Observationsmentioning
confidence: 90%
“…Various methods have been employed to culture and enrich anammox biomass, e.g. anammox biomass has been enriched from different types of inoculums-sludge from anaerobic (Tsushima et al 2007a) or nitrifying/ denitrifying reactors (Jeanningros et al 2010;Desloover et al 2011;Gaul et al 2005;Tang et al 2010b). To our knowledge enrichment of anammox microorganisms directly from wastewater on biofilm carrier elements without using seeding sludge has not been reported in previous studies.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is an advantage because the production of surplus sludge is reduced; however, it also implies that the process must be operated in reactors with very good sludge retention. Some of the systems used to improve biomass retention are based on biofilm reactors, either with moving bed carriers [2][3][4][5][6] or fixedbed systems [7][8][9][10]. The formation of bacterial biofilms must, necessarily, begin with the adhesion of a small number of bacterial cells to a surface [11].…”
Section: Introductionmentioning
confidence: 99%